Catalyst for preparing ethanol by hydrogenation of methyl acetate and application of catalyst
By using Al2O3 support and alkali-etched CuOx-ZnO/Al2O3 catalyst modified in methyl acetate hydrogenation reaction, the complex catalyst preparation and environmentally unfriendly problems in the prior art were solved, and high conversion rate and selectivity were achieved. Maintain stability during long-term reactions and is suitable for industrial production.
Patent Information
- Application Number
- CN202411408777.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
AI Technical Summary
The existing catalyst preparation process of hydrogenation of methyl acetate to ethanol has problems such as high equipment requirements, unfriendly environment, high cost and insufficient catalytic activity, and lacks a simple, easy to operate, environmentally friendly and efficient catalyst.
Al2O3 is used as a support to prepare CuOx-ZnO/Al2O3 catalyst by alkali etching modification and deposition-co-precipitation method. The additive ZnO is added to uniformly distribute Cu elements to avoid Cu agglomeration. It is applied under high temperature and high pressure conditions after tableting molding.
The conversion rate of methyl acetate reached 99.3%, the selectivity of ethanol reached 93.8%, and the stable performance was maintained in 400 hours of reaction. The preparation process was simple and low-cost, which was suitable for industrial applications.
Smart Images

Figure BDA0005077417500000071 
Figure BDA0005077417500000081 
Figure BDA0005077417500000082
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of catalysts, and in particular to a catalyst for hydrogenating methyl acetate to produce ethanol and its application. Background Art
[0002] Ethanol is a very important chemical raw material, which is widely used in today's society, especially in the fields of food industry, medical health, agricultural production and chemical industry. At present, there are three main ways to produce ethanol in industry, namely grain fermentation, ethylene direct hydration and coalification. However, on the one hand, grain fermentation requires a large amount of grain, which has the disadvantage of competing with people for grain; on the other hand, the raw material ethylene in the ethylene direct hydration method is taken from petroleum cracking gas, which runs counter to the basic national conditions of less oil and poor gas; on the other hand, the coalification method has the following disadvantages: for areas with rich coal resources, the coalification method for preparing ethanol cannot be developed rapidly because of the small consumer market and the incomplete downstream supporting equipment. For areas with larger consumer markets, the scarce coal resources and the high cost of transporting coal resources have increased costs, thus affecting the competitiveness of coal-based ethanol in the domestic and international markets.
[0003] In recent years, there have been many reports on the direct or indirect catalytic hydrogenation of acetic acid to produce ethanol. Specifically, the corrosive acetic acid is first converted into non-corrosive methyl acetate, and then the methyl acetate is catalytically hydrogenated to produce ethanol. This scheme has low requirements for equipment, and the catalyst is a non-precious metal catalyst. Because of its low production cost, it has great prospects for industrial production.
[0004] At present, Cu catalyst is widely used in industry as a catalyst for hydrogenation of methyl acetate to produce ethanol.
[0005] The related art discloses a copper-zinc silicon dioxide catalyst for producing ethanol by hydrogenation of methyl acetate and a preparation method thereof. 2 As a carrier, Cu and Zn active ingredients are loaded, the total mass fraction of Cu and Zn accounts for 30%, and the molar ratio of Cu and Zn is 14-7. In the hydrogenation reaction, the conversion rate of methyl acetate is 91.2%, the selectivity of ethanol is 89%, and the catalyst performance remains unchanged after 100 hours of reaction. However, a large amount of ethanol solution needs to be added during the catalyst preparation process to inhibit the in-situ hydrolysis of ethyl orthosilicate to form a carrier.
[0006] The related art also discloses a catalyst for hydrogenating methyl acetate to ethanol and its application. In this scheme, the catalyst includes one or two of Cu, Zn, Mn, and La oxides, and SiO 2As the carrier, it is prepared by co-precipitation-ammonia evaporation method. However, the ammonia evaporation process will release a large amount of ammonia gas, and it takes a long time, which is not environmentally friendly. At the same time, the preparation conditions are also relatively harsh.
[0007] In addition, the related art also discloses a catalyst for preparing ethanol by hydrogenation of methyl acetate and a preparation method thereof. In this scheme, the catalyst is a metal-doped copper-zinc-aluminum catalyst, which is prepared by a step-by-step precipitation method, wherein aluminum, doped metal, and copper-zinc are sequentially precipitated with sodium carbonate. The preparation process of the catalyst in this scheme is relatively complicated.
[0008] Therefore, it is urgent to develop a catalyst for hydrogenating methyl acetate to ethanol that has a simple preparation method, is easy to operate, is environmentally friendly, has low cost and has excellent catalytic activity. Summary of the invention
[0009] The present application provides a catalyst for hydrogenating methyl acetate to produce ethanol, and a preparation method and application thereof. The catalyst preparation method is simple, easy to operate, environmentally friendly, low in cost, and has excellent catalytic activity, and has good industrial application prospects.
[0010] This application systematically studies the influence of the proportion of metal Cu in the catalyst and the ratio of Cu and Zn on the performance of the catalyst. First, the surface of the carrier is modified by alkaline etching to create stable anchoring points for the active components; then the catalyst is prepared by the deposition-coprecipitation method to retain all the active components on the surface and improve the utilization rate of the active components. In addition, the addition of additives makes the Cu element in the catalyst evenly distributed and controllable in size, avoiding the agglomeration of Cu at high content. The tablet-formed catalyst was crushed and applied to the hydrogenation reaction of methyl acetate. At a reaction temperature of 225°C and a pressure of 3MPa, the conversion rate of methyl acetate reached 99.3%, and the selectivity of ethanol reached 93.8%. During the 400h evaluation reaction process, the performance was relatively stable.
[0011] In a first aspect, the present application provides a catalyst for hydrogenating methyl acetate to ethanol, using the following technical solution:
[0012] A catalyst for preparing ethanol by hydrogenating methyl acetate, the catalyst comprising a carrier, an active component supported on the carrier and an auxiliary agent; the carrier is Al 2 O 3 ; The active component is CuO x (x≤1); the auxiliary agent is ZnO; in terms of oxide weight percentage, the CuO x Accounting for 10-60%, the Al 2 O 3 20% and the rest is ZnO;
[0013] The catalyst is prepared by a deposition-coprecipitation method; the preparation method of the catalyst specifically comprises the following steps:
[0014] First, pseudo-boehmite is dissolved in a sodium bicarbonate solution to prepare a suspension, a soluble copper salt and a soluble zinc salt are used to prepare a 1-1.5 mol / L salt solution, and an alkali solution with the same concentration as the salt solution is prepared;
[0015] Then, the salt solution and the alkaline solution are added dropwise to the suspension, and the suspension is aged and filtered in sequence, and the filter cake is repeatedly slurried and filtered to obtain a coprecipitated product;
[0016] Finally, the coprecipitated product is dried, ground, granulated, and calcined at 300-600° C. to decompose. The decomposition product obtained is evenly mixed with a molding agent, and pressed into tablets to obtain a catalyst.
[0017] The typical structure of pseudo-boehmite is an extremely thin folded layer. It is an aluminum oxide hydrate with a special spatial network structure. It has physical properties such as high specific surface area and large pore volume, which make it an ideal choice for catalyst carriers. Aluminum sol can also be used as an aluminum source, but the product is very corrosive. During heating and use, it will also release a large amount of highly corrosive HCl gas. Therefore, when choosing alumina as a carrier, pseudo-boehmite is preferred.
[0018] Sodium bicarbonate can theoretically be replaced by sodium carbonate, which is also a weak base. Data show the relationship between the concentration of sodium carbonate solution and pH: According to experimental results, the pH value of a saturated solution of carbon dioxide is about 4.0, while the pH value of a 0.1 mol / L sodium carbonate solution is 11.63. Therefore, changes in the pH value of the solution will cause changes in the existence form of carbon dioxide, sodium bicarbonate, and sodium carbonate in the sodium carbonate solution. When the pH of the solution is less than 4.0, the main component is carbon dioxide. In the pH range of 4.0-11.63, sodium bicarbonate is mainly present. When the pH of the solution is greater than 11.63, the main component is sodium carbonate. Therefore, if the pseudo-boehmite is surface modified in a weak alkaline solution, it is more appropriate to choose sodium bicarbonate.
[0019] Optionally, the pH of the sodium bicarbonate solution is 8.3.
[0020] Optionally, the concentration of sodium bicarbonate in the sodium bicarbonate solution is 0.0025-0.1 mol / L.
[0021] Optionally, the pseudo-boehmite dispersed in the sodium bicarbonate solution is pseudo-boehmite from which organic impurities remaining in the preparation process are removed after calcination.
[0022] Optionally, the calcination temperature of the pseudo-boehmite is 400-700°C.
[0023] Optionally, the calcination temperature of the pseudo-boehmite is 500-600°C.
[0024] Optionally, the calcination time of the pseudo-boehmite is 2-4 hours.
[0025] Optionally, the calcination time of the pseudo-boehmite is 0.5-1h.
[0026] Optionally, the atmosphere used for the calcination is air.
[0027] Optionally, the soluble copper salt includes any one or more of copper chloride, copper acetate, and copper nitrate.
[0028] Optionally, the soluble zinc salt includes any one or more of zinc chloride, zinc acetate, and zinc nitrate.
[0029] Optionally, the alkaline solution includes any one or more of sodium carbonate, sodium bicarbonate and sodium hydroxide solution.
[0030] Optionally, the molding agent includes any one or more of graphite, magnesium stearate, and calcium stearate.
[0031] Optionally, the molding agent is graphite.
[0032] In a specific embodiment, the preparation method of the catalyst is as follows:
[0033] (1) dispersing pseudo-boehmite in a sodium bicarbonate solution, and stirring the solution in a water bath at 60-80° C. for 0.5-1 h to obtain a uniform suspension; preparing a 1-1.5 mol / L salt solution using a soluble copper salt and a soluble zinc salt, and simultaneously preparing an alkali solution of the same concentration;
[0034] (2) adding the salt solution and the alkaline solution dropwise to the suspension, maintaining stirring during the addition process, at a temperature of 60-80° C. and a pH of 7-7.5, to obtain a slurry;
[0035] (3) aging the slurry at 60-80° C. for 2-6 hours, filtering after aging to retain the filter cake, and slurrying and filtering the filter cake with water, repeating the process 5-10 times to obtain a coprecipitated product;
[0036] (4) drying the coprecipitated product at 100-140° C., grinding, granulating, and calcining and decomposing at 300-600° C. for 2-6 hours to obtain a decomposition product;
[0037] (5) The decomposition product and the molding agent are uniformly mixed in a weight ratio of 100:(1-3), and pressed into tablets to obtain a catalyst.
[0038] Optionally, the catalyst needs to be subjected to reduction activation treatment before use.
[0039] Optionally, the reduction activation treatment conditions are: temperature of 170-230°C, reducing atmosphere of H 2 and N 2 Mixed gas, of which H 2 The volume fraction is 5-10%.
[0040] In a second aspect, the present application provides an application of the above-mentioned catalyst in the hydrogenation of methyl acetate to ethanol.
[0041] In a third aspect, the present application provides a method for producing ethanol by hydrogenating methyl acetate, wherein the above-mentioned catalyst is used.
[0042] Optionally, the process conditions in the method include: methyl acetate is reacted with methyl acetate for 0.5-2h -1 The mass space velocity was passed into the continuous fixed bed reactor, and H 2 , control the molar ratio of hydrogen to ester to be 10-100, and carry out the reaction at a reaction temperature of 180-240°C and a reaction pressure of 3-5MPa.
[0043] In the method for preparing ethanol by hydrogenation of methyl acetate provided in the present application, CuO x -ZnO / Al 2 O 3 As a catalyst, the methyl acetate was hydrogenated to produce ethanol at a temperature of 180-240°C and a pressure of 3-5MPa. The methyl acetate conversion rate reached 99.3%, and the ethanol selectivity reached 93.8%. During the 400h evaluation reaction, the performance was relatively stable.
[0044] In summary, the present application includes at least one of the following beneficial technical effects:
[0045] 1. The present application uses a deposition-coprecipitation method to retain all active components on the surface, thereby improving the utilization rate of active components. At the same time, the surface of the carrier is modified by alkaline etching to create a stable anchoring point for the active component. In addition, the addition of additives makes the Cu element in the catalyst evenly distributed and controllable in size, avoiding the agglomeration of Cu at high content.
[0046] 2. The catalyst of the present application enables the methyl acetate conversion rate to reach over 99.0%, and the ethanol selectivity to reach 93.8%, and the performance is stable during the 400h evaluation process.
[0047] 3. The methyl acetate hydrogenation catalyst provided in the present application is not only simple to prepare and easy to operate, but also has high activity, high selectivity and high stability. DETAILED DESCRIPTION
[0048] Before describing the embodiments of the present application in detail, it should be understood that the terms used herein are only used for the purpose of describing specific embodiments. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by ordinary technicians in the field to which the terms belong.
[0049] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.
[0050] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0051] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0052] The present application provides a catalyst for hydrogenating methyl acetate to produce ethanol. The catalyst comprises a carrier, an active component supported on the carrier, and an additive. The carrier is Al 2 O 3 , the active component is CuO x (x≤1), the additive is ZnO. In terms of oxide weight percentage, CuO x 10-60%, Al 2 O 3 It accounts for 20% and the rest is ZnO.
[0053] The above catalyst is prepared by a deposition-coprecipitation method, and the preparation method specifically comprises the following steps:
[0054] First, pseudo-boehmite is dissolved in a sodium bicarbonate solution to prepare a suspension, a soluble copper salt and a soluble zinc salt are used to prepare a 1-1.5 mol / L salt solution, and an alkali solution with the same concentration as the salt solution is prepared;
[0055] Then, the salt solution and the alkaline solution are added dropwise to the suspension, and the suspension is aged and filtered in sequence, and the filter cake is repeatedly slurried and filtered to obtain a coprecipitated product;
[0056] Finally, the coprecipitated product is dried, ground, granulated, and calcined at 300-600°C for decomposition. The decomposition product obtained is evenly mixed with a molding agent, and pressed into tablets to obtain a catalyst.
[0057] In a specific embodiment, the preparation method of the above catalyst specifically comprises the following steps:
[0058] (1) Pseudo-boehmite is placed in a muffle furnace and calcined at 400-700°C in an air atmosphere for 2-4 hours. The calcined pseudo-boehmite is dispersed in a 0.0025-0.1 mol / L sodium bicarbonate solution (pH 8.3) and stirred in a water bath at 60-80°C for 0.5-1 hour to obtain a uniform suspension.
[0059] (2) Use soluble copper salt and soluble zinc salt to prepare a 1-1.5 mol / L salt solution.
[0060] (3) Prepare an alkaline solution with the same concentration as the salt solution.
[0061] (4) adding the salt solution and the alkaline solution dropwise to the suspension, maintaining stirring during the addition process, the temperature is 60-80° C., and the pH is 7-7.5 to obtain a slurry;
[0062] (5) aging the slurry at 60-80° C. for 2-6 h, filtering after aging to retain the filter cake, and slurrying and filtering the filter cake with water, repeating this process 5-10 times to obtain a coprecipitated product;
[0063] (6) drying the coprecipitated product at 100-140° C., grinding, granulating, and calcining and decomposing at 300-600° C. for 2-6 hours to obtain a decomposition product;
[0064] (7) The decomposition product and the molding agent are uniformly mixed in a weight ratio of 100:(1-3), and pressed into tablets to obtain a catalyst.
[0065] Wherein, the soluble copper salt includes any one or more of copper chloride, copper acetate, and copper nitrate. The soluble zinc salt includes any one or more of zinc chloride, zinc acetate, and zinc nitrate. The alkaline solution includes any one or more of sodium carbonate, sodium bicarbonate, and sodium hydroxide solution. The molding agent includes any one or more of graphite, magnesium stearate, and calcium stearate.
[0066] The present application also provides a method for preparing ethanol by hydrogenating methyl acetate, wherein the above catalyst is used.
[0067] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme in the embodiment of the present application will be clearly and completely described below. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. The embodiments described below are exemplary and are only used to explain the present application to illustrate catalyst components and preparation process, and cannot be interpreted as limiting the present application.
[0068] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0069] The present application is further described in detail below in combination with embodiments, comparative examples and test results.
[0070] Example
[0071] Example 1
[0072] This embodiment provides a catalyst for hydrogenating methyl acetate to ethanol.
[0073] The preparation method of the above catalyst specifically comprises the following steps:
[0074] (1) Pseudo-boehmite was placed in a muffle furnace and calcined at 550°C in an air atmosphere for 2 h. 20 g of the calcined pseudo-boehmite was dispersed in 150 mL of 0.1 mol / L sodium bicarbonate solution (pH 8.3) and stirred in a water bath at 70°C for 1 h to obtain a uniform suspension.
[0075] (2) Take 30.2 g of analytical pure copper nitrate trihydrate and 256.9 g of zinc nitrate hexahydrate, add 989 mL of deionized water, and prepare a 1 mol / L salt solution.
[0076] (3) Take 104.8 g of anhydrous sodium carbonate and add 989 mL of deionized water to prepare a 1 mol / L alkaline solution.
[0077] (4) The salt solution of step (2) and the alkaline solution of step (3) are added dropwise to the suspension of step (1) by a peristaltic pump, and stirring is continued during the addition process. The water bath temperature is maintained at 70° C. and the pH is always maintained at 7 to obtain a slurry.
[0078] (5) The slurry of step (4) is aged in a water bath at 70° C. for 2 h. After aging, the slurry is filtered to retain the filter cake, and the filter cake is slurried and filtered with water, and the process is repeated 5-10 times to obtain a coprecipitated product.
[0079] (6) The coprecipitated product of step (5) is placed in an oven at 120° C. and dried for 8 h, ground, granulated, and calcined in a muffle furnace at 400° C. for 2 h to obtain a decomposition product (the powder after grinding is ensured to have no granular feel, and the particle size of the particles obtained by granulation is required to be ≤20 mesh).
[0080] (7) The decomposition product of step (6) is mixed evenly with graphite in a weight ratio of 100:1, and pressed into tablets to prepare a catalyst. In which, in terms of oxide weight percentage, CuO: ZnO: Al 2 O 3 =1:7:2.
[0081] Embodiment 2-8
[0082] Examples 2-8 each provide a catalyst for hydrogenating methyl acetate to ethanol.
[0083] The difference between the preparation method of the above catalyst and that of Example 1 is that the weight of the compounds used to prepare the salt solution and the alkaline solution and the decomposition temperature are specifically shown in Table 1. The rest are consistent with the operating steps of Example 1.
[0084] The differences between the above embodiments 1-8 are as follows:
[0085] The difference between Examples 1-6 lies in the weight of the compounds used to prepare the salt solution and the alkaline solution.
[0086] The difference between Examples 4 and 7-8 is the decomposition temperature.
[0087] Comparative Example
[0088] Comparative Example 1
[0089] This comparative example provides a catalyst for hydrogenating methyl acetate to ethanol.
[0090] The difference between the preparation method of the above catalyst and that of Example 1 is that the liquid used to disperse the pseudo-boehmite is specifically shown in Table 1. The rest of the steps are consistent with those of Example 1.
[0091] Comparative Example 2
[0092] This comparative example provides a catalyst for hydrogenating methyl acetate to ethanol.
[0093] The difference between the preparation method of the above catalyst and that of Example 1 is that the salt solution prepared contains only copper nitrate trihydrate and no zinc nitrate hexahydrate, as shown in Table 1. The rest of the steps are the same as those of Example 1.
[0094] Table 1 Type and amount of each component in the catalyst of each embodiment and comparative example and some preparation parameters
[0095]
[0096]
[0097] Performance testing
[0098] (I) Catalyst performance testing
[0099] The catalytic performance of the catalysts provided in the above examples and comparative examples was evaluated and analyzed by preparing ethanol, and the test results are shown in Table 2.
[0100] The evaluation method is as follows:
[0101] The above catalyst was crushed into 10-40 meshes, and 20 mL was weighed and loaded into the reaction tube. The catalyst bed height was 10 cm. The raw material used was industrial methyl acetate. Shimadzu gas chromatograph was used to conduct qualitative and quantitative analysis of the product components. 20 mL of the catalyst was loaded into a fixed bed reactor. The catalyst was reduced and activated at normal pressure and 170-230 ° C. The reducing atmosphere was H 2 / N 2 The mixed gas, H 2 The volume percentage is 5-10%. Under the conditions of temperature 225℃ and pressure 3MPa, methyl acetate is heated for 0.5-2h. -1 The mass space velocity was passed into the continuous fixed bed reactor, and H 2 , control the molar ratio of hydrogen to ester to 10-100, and carry out hydrogenation reaction.
[0102] The calculated results of feedstock conversion and product selectivity are shown in Table 2.
[0103] Table 2 Feedstock conversion and product selectivity in ethanol preparation using catalysts provided in Examples and Comparisons
[0104]
[0105] As can be seen from Table 2, the conversion rates of the catalysts prepared in this application are all above 90%, and the ethanol selectivity is all above 86.3%. In particular, the catalyst conversion rate of Example 4 of this application is above 99%, and the ethanol selectivity is above 93%. In contrast, the catalyst conversion rates in the comparative examples are 87.4% and 70.1%, respectively, and the ethanol selectivity is 80.9% and 77.6%, respectively, which are all inferior to the catalysts prepared in this application, indicating that failure to modify the surface of the carrier and failure to add an auxiliary agent will significantly reduce the catalytic performance of the catalyst. By comparing Examples 1-6, it can be seen that too little or too much Cu content in the catalyst will affect the performance of the catalyst.
[0106] By comparing Example 4 with Examples 7-8, it can be seen that the decomposition temperature significantly affects the catalytic performance of the catalyst. If the temperature is too low, the catalyst will not be completely decomposed; if the temperature is too high, the catalyst will easily sinter and agglomerate.
[0107] (II) Evaluation of catalyst service life
[0108] The service life of the catalyst provided in Example 4 was investigated. The evaluation results are shown in Table 3.
[0109] Table 3 Evaluation results of catalyst service life
[0110] Reaction time (h) Methyl acetate conversion rate (%) Ethanol selectivity (%) Methanol selectivity (%) 100 99.3 93.8 92.9 200 99.2 93.8 92.8 300 98.9 93.6 92.8 400 98.7 93.6 92.5
[0111] As can be seen from Table 3, the catalytic performance of the catalyst prepared in Example 4 was only slightly reduced after being used for 400 hours, which shows that the catalyst provided in the present application has not only excellent catalytic performance but also a longer service life.
[0112] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A catalyst for hydrogenating methyl acetate to ethanol, characterized in that: The catalyst comprises a carrier, an active component supported on the carrier and an additive; the carrier is Al2O3; the active component is CuO x (x≤1); the auxiliary agent is ZnO; in terms of oxide weight percentage, the CuO x Accounting for 10-60%, the Al2O3 accounts for 20%, and the rest is the ZnO; The catalyst is prepared by a deposition-coprecipitation method; the preparation method of the catalyst specifically comprises the following steps: First, pseudo-boehmite is dissolved in a sodium bicarbonate solution to prepare a suspension, a soluble copper salt and a soluble zinc salt are used to prepare a 1-1.5 mol / L salt solution, and an alkali solution with the same concentration as the salt solution is prepared; Then, the salt solution and the alkaline solution are added dropwise to the suspension, and the suspension is aged and filtered in sequence, and the filter cake is repeatedly slurried and filtered to obtain a coprecipitated product; Finally, the coprecipitated product is dried, ground, granulated, and calcined at 300-600° C. to decompose. The decomposition product obtained is evenly mixed with a molding agent, and pressed into tablets to obtain a catalyst.
2. The catalyst according to claim 1, characterized in that The pH of the sodium bicarbonate solution is 8.3; Optionally, the concentration of sodium bicarbonate in the sodium bicarbonate solution is 0.0025-0.1 mol / L.
3. The catalyst according to claim 1, characterized in that The pseudo-boehmite dispersed in the sodium bicarbonate solution is the pseudo-boehmite from which organic impurities remaining in the preparation process are removed after calcination.
4. The catalyst according to claim 3, characterized in that The calcination temperature of the pseudo-boehmite is 400-700°C; Optionally, the calcination temperature of the pseudo-boehmite is 500-600°C; Optionally, the calcination time of the pseudo-boehmite is 2-4h; Optionally, the calcination time of the pseudo-boehmite is 0.5-1h; Optionally, the atmosphere used for the calcination is air.
5. The catalyst according to claim 1, characterized in that The soluble copper salt includes any one or more of copper chloride, copper acetate, and copper nitrate; Optionally, the soluble zinc salt includes any one or more of zinc chloride, zinc acetate, and zinc nitrate; Optionally, the alkaline solution includes any one or more of sodium carbonate, sodium bicarbonate and sodium hydroxide solution; Optionally, the molding agent includes any one or more of graphite, magnesium stearate, and calcium stearate; Optionally, the molding agent is graphite.
6. The catalyst according to claim 1, characterized in that The preparation method of the catalyst is as follows: (1) Disperse pseudo-boehmite in a sodium bicarbonate solution and stir in a water bath at 60-80°C for 0.5-1h to obtain a uniform suspension; prepare a 1-1.5 mol / L salt solution using a soluble copper salt and a soluble zinc salt, and simultaneously prepare an alkali solution of the same concentration; (2) adding the salt solution and the alkaline solution dropwise to the suspension, maintaining stirring during the dropping process, the temperature is 60-80° C., and the pH is 7-7.5, to obtain a slurry; (3) aging the slurry at 60-80° C. for 2-6 hours, filtering after aging to retain the filter cake, and slurrying and filtering the filter cake with water, repeating the process 5-10 times to obtain a coprecipitated product; (4) drying the coprecipitated product at 100-140° C., grinding, granulating, and calcining and decomposing at 300-600° C. for 2-6 hours to obtain a decomposition product; (5) The decomposition product and the molding agent are uniformly mixed in a weight ratio of 100:(1-3), and pressed into tablets to obtain a catalyst.
7. The catalyst according to claim 1, characterized in that The catalyst needs to be reduced and activated before use; Optionally, the conditions for the reduction activation treatment are: a temperature of 170-230° C., a reducing atmosphere of a mixture of H 2 and N 2 , wherein the volume fraction of H 2 is 5-10%.
8. Use of the catalyst according to any one of claims 1 to 7 in hydrogenating methyl acetate to ethanol.
9. A method for preparing ethanol by hydrogenating methyl acetate, characterized in that: The method uses the catalyst according to any one of claims 1 to 7.
10. The method according to claim 9, characterized in that The process conditions of the method include: methyl acetate is reacted with methyl acetate for 0.5-2h -1 The mass space velocity is introduced into a continuous fixed bed reactor, and H2 is continuously introduced to control the molar ratio of hydrogen to ester to be 10-100. The reaction is carried out at a reaction temperature of 180-240°C and a reaction pressure of 3-5MPa.